2011
DOI: 10.2337/db10-0924
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Inactivation of the Na/Ca Exchanger Increases Glucose-Induced Insulin Release, β-Cell Proliferation, and Mass

Abstract: OBJECTIVEWe have previously shown that overexpression of the Na-Ca exchanger (NCX1), a protein responsible for Ca2+ extrusion from cells, increases β-cell programmed cell death (apoptosis) and reduces β-cell proliferation. To further characterize the role of NCX1 in β-cells under in vivo conditions, we developed and characterized mice deficient for NCX1.RESEARCH DESIGN AND METHODSBiologic and morphologic methods (Ca2+ imaging, Ca2+ uptake, glucose metabolism, insulin release, and point counting morphometry) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…2c). The observed ultrastructure perfectly matched the ultrastructure described in the literature [5]. A non-quantitative electron microscopy examination of the samples demonstrated no obvious differences between Pmca2…”
Section: +/− Islets (Batches Of Ten Islets Four and Five Individual supporting
confidence: 86%
See 2 more Smart Citations
“…2c). The observed ultrastructure perfectly matched the ultrastructure described in the literature [5]. A non-quantitative electron microscopy examination of the samples demonstrated no obvious differences between Pmca2…”
Section: +/− Islets (Batches Of Ten Islets Four and Five Individual supporting
confidence: 86%
“…In a previous study in mice [5], we showed that heterozygous inactivation of the Na/Ca exchanger (isoform 1: NCX1), a protein responsible for Ca 2+ extrusion from cells [6,7], induced several modifications of the beta cell including an increase in glucose-induced insulin release and beta cell proliferation and mass. Ncx1 +/− islets also displayed an increased resistance to hypoxia and when transplanted into diabetic animals produced a four to seven times higher rate of diabetes cure than Ncx1 +/+ islets [5]. Another mechanism responsible for Ca 2+ extrusion from cells is the plasma membrane Ca 2+ -ATPase (PMCA) [8].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 97%
See 1 more Smart Citation
“…As noted above, activation of voltage-gated Ca 2+ channels leads to increased intracellular Ca 2+ , a sufficient signal for insulin secretion and cell proliferation (37). Increased expression of CACNA2D2 has previously been shown to increase intracellular Ca 2+ (38), providing a potential link between increased expression of CACNA2D2 and increased insulin secretion and/or cell proliferation.…”
Section: Altered Gene Expression In Tumors With Yy1 T372rmentioning
confidence: 90%
“…1 Dyssynchronous activation of ventricular tissue, as it occurs in bundle-branch block, leads to less efficient contraction and worsening of heart failure, whereas resynchronization therapy improves cardiac contractility, morbidity, and mortality in these patients. 2 Dyssynchronous contraction is also observed in hearts with diastolic or systolic heart failure in the absence of overt electric conduction defects, 3 suggesting dysfunction at the level of the cardiomyocyte.…”
mentioning
confidence: 99%